Electromyographic signature of isometric squat in the highest refuge in Europe - Riccardo Rua; Danilo Bondi; Carmen Santangelo; Pamela Pignatelli; Tiziana Pietrangelo; Stefania Fulle; Vito Fanelli; Vittore Verratti (PAGEPress Publications, 2023)
Reports of electromyography during hypoxic exercise are contrasting, due to protocol and muscle diversity. This work aimed to investigate alterations in muscle activation and myoelectrical fatigue during exercise at high-altitude in those muscles primarily involved in trekking. Twelve young adults balanced by gender and age were tested at low (1,667 m) and high (4,554 m, "Capanna Margherita", Italy) altitude, during an isometric squat lasting 60 seconds. High-density surface electromyography was performed from the quadriceps of right limb. The root mean square (RMS), median frequency with its slope, and muscle fiber conduction velocity (MFCV) were computed. Neither males nor females showed changes in median frequency (Med: 36.13 vs 35.63 Hz) and its slope (Med: -9 vs -12 degree) in response to high-altitude trekking, despite a great inter-individual heterogeneity, nor differences were found for MFCV. RMS was not significantly equivalent, with greater values at low altitude (0.385 ± 0.104 mV) than high altitude (0.346 ± 0.090 mV). Unexpected results can be due either to a postural compensation of the whole body compensating for a relatively greater effort or to the inability to support muscle activation after repeated physical efforts.  Interesting results may emerge by measuring simultaneously electromyography, muscle oxygenation and kinematics comparing trekking at normoxia vs hypoxia.